Development Strategy of Mangrove Crabs (Scylla sp.) Cultivation in Gorontalo Province - Yuniarti Koniyo (Journal Omni-Akuatika, 2020)
Mangrove crabs (Scylla sp.) are important economic fishery commodities that will be developed in Gorontalo Province. Mangrove crabs have large and prospective market opportunities in the domestic and foreign market. The mangrove crabs demand in this country is very high. Market demand for mangrove crabs has not been able to be fulfilled, because of the limited catch and the production of aquaculture which is still very minimal. The problem is how the development of mangrove crab cultivation will be applied in Gorontalo Province. The purpose of this research was to study and determine the development strategy of mangrove crab cultivation in Gorontalo Province in accordance with the potential and carrying capacity of the environment. The researched method was survey method with observational data collection and random sampling techniques. Data analysis was performed descriptively and SWOT analysis. Based on the SWOT analysis the strength (S) most influential on the development of mangrove crab culture in Gorontalo Province is government support and profitable business prospects (0.66), while the biggest weakness is the limited capital (0.54) and the low quality of human cultivation resources (0,48), and the biggest opportunity (O) is economic value (Very popular, because it is delicious and contains high nutritional value) (0.8), and threat (T) environmental degradation (0.8). Based on the quadrant of the analysis is in quadrant 1 (Growth Oriented Strategy). Keywords: Development, Strategy, Scylla spp, Cultivation, Gorontalo Province